Human Macrophage Galactose‐Type Lectin (MGL) Recognizes the Outer Core of Escherichia coli Lipooligosaccharide. (24th June 2019) - Maalej, Meriem; Forgione, Rosa Ester; Marchetti, Roberta; Bulteau, François; Thépaut, Michel; Lanzetta, Rosa; Laguri, Cedric; Simorre, Jean‐Pierre; Fieschi, Franck; Molinaro, Antonio; Silipo, Alba
Abstract: Carbohydrate–lectin interactions intervene in and mediate most biological processes, including a crucial modulation of immune responses to pathogens. Despite growing interest in investigating the association between host receptor lectins and exogenous glycan ligands, the molecular mechanisms underlying bacterial recognition by human lectins are still not fully understood. Herein, a novel molecular interaction between the human macrophage galactose‐type lectin (MGL) and the lipooligosaccharide (LOS) of Escherichia coli strain R1 is described. Saturation transfer difference NMR spectroscopy analysis, supported by computational studies, demonstrated that MGL bound to the purified deacylated LOSR1 mainly through recognition of its outer core and established crucial interactions with the terminal Galα(1, 2)Gal epitope. These results assess the ability of MGL to recognise glycan moieties exposed on Gram‐negative bacterial surfaces. Abstract : Distinguishing features : Carbohydrate–lectin interactions intervene in and mediate most biological processes. From results of saturation transfer difference NMR spectroscopy and computational studies, the ability of human macrophage galactose‐type lectin (h‐MGL) to recognise glycan moieties exposed on the lipooligosaccharide (LOS) of E. coli strain R1 is revealed.